To Study The Correlation Between Preoperative Inferior Vena Cava Diameter And Intraoperative Hypotension During Spinal Anaesthesia In Caesarean Section. (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: Assessment of maternal intravascular volume status during and after gestation is most crucial  in the setting of complications that affect hemodynamic stability. The goal of the perioperative fluid management  is to avoid acute kidney injury due to hypovolemia and hypotension due to spinal anaesthesia. Ultrasound  measurements of dynamic change in inferior vena cava diameter (IVC) and collapsibility index are used to predict  and prevent the hypotension after spinal anaesthesia. OBJECTIVES: To correlate the IVC diameter in expiration and incidences of intraoperative hypotension after  spinal anaesthesia in full term pregnant patients posted for elective caesarean section. MATERIALS AND METHOD: Total 50 young female patients having full term pregnancy scheduled for  elective caesarean sections were included in the study after taking informed consent. Preoperative assessment of  all patients was done. Preoperative inferior vena cave diameter in expiration was measured by ultrasound guidance  by subcostal approach. Spinal anaesthesia was given with injection bupivacaine heavy 0.5% 2ml between L3-L4  subarachnoid space after taking all aseptic precaution. Pulse, blood pressure was measured at regular interval.  Incidence of intraoperative hypotension, bradycardia was noted. Results were expressed as mean ±SD and  analysed by paired’ test and correlation coefficient was calculated. RESULTS: The mean inferior vena cava diameter in expiration was 17.4 ± 0.04 and collapsibility index was less  than 36 in 80% of patients, and only one patient had developed hypotension after spinal anaesthesia. Correlation  coefficient was -0.9. CONCLUSION: Preoperative inferior vena cava measurement is a reliable predictor of hypotension after spinal  anaesthesia.
Keywords: Ultrasound; IVC collapsibility index; pregnant patients; spinal anaesthesia